The Landscape and Prognosis Potential of the T-Cell Repertoire in Membranous Nephropathy - Zhang, Yu; Jin, Yabin; Guan, Zhanwen; Li, Huishi; Su, Zuhui; Xie, Chao; Chen, Xiangping; Liu, Xiaofen; Pan, Yingming; Ye, Peiyi; Zhang, Lifang; Kong, Yaozhong; et al. (Frontiers in Immunology, 2020)
Membranous nephropathy (MN), a common pathological type of adult nephrotic syndrome, is an antibody-mediated kidney disease. It is widely accepted now that the MN is an immune related disease with the involvement of the whole immune system. In this study, we analyzed the T cell receptor beta chain (TCRβ) repertoire of the circulating T lymphocytes of MN patients and healthy controls using high throughput sequencing. We compared multiple aspects of TCRβ repertoire, including diversity and Vβ, Jβ gene between MN patients and healthy controls and we found that the diversities of VJ cassette combination in peripheral blood of MN patients were lower than healthy controls. We also found the TCRβ repertoire similarity between pre- and post-therapy could reflect the clinical outcome and two Vβ genes in pre-therapy had potential to predict the therapeutic effect. These findings indicated the potential of TCRβ repertoire as non-invasive biomarkers for the prognosis prediction of MN. The characteristics of circulating T lymphocytes repertoires shed light on MN detection, treatment and surveillance.